Zinc Element Traces to Inhibit Scale Formation on Cooling Tower and Air Cooler Systems - Abdul Rahman Ahmed Reshan, Shaymaa (Iraqi Journal of Chemical and Petroleum Engineering, 2013)
Calcium carbonate is predominantly present in aqueous systems, which is commonly used in industrial processes. It has inverse solubility characteristics resulting in the deposition of scale on heat transfer surface. This paper focuses on developing methods for inhibition of calcium carbonate scale formation in cooling tower and air cooler system where scaling can cause serious problems, ZnCl 2 and ZnI 2 has been investigated as scale inhibitor on AISI 316 and 304. ZnCl 2 were more effective than ZnI 2 in both systems, and AISI 316 show more receptivity to the chlorides salt compared to AISI 304. The inhibitors were more effective in cooling tower than air cooler system. AISI 316 show more constant inhibition efficiency in cooling tower with maximum of 95% with ZnCl 2 and 83% with ZnI 2 .